Influence of Ground Motion Duration on Responses of Concrete Gravity Dams - Wang, C.; Hao, Hong; Zhang, S.; Wang, G. (Taylor & Francis Ltd., 2018)
This study investigates the duration effect on the responses and damage of a dam–reservoir–foundation system. A group of 95 recorded accelerograms with a wide range of durations are adopted in the analyses. A novel global damage index that takes into consideration the consequences of damage at different locations on the overall dam safety is proposed. Nonlinear analysis results show that the duration is positively correlated with the accumulated damage of the dam system. An amplification coefficient that relates the response of the concrete gravity dam from short-duration and long-duration ground motions is proposed.